Detection of the origin of atrial tachycardia by 3D electro‐anatomical mapping and treatment by radiofrequency catheter ablation in horses. (9th June 2022) - Van Steenkiste, Glenn; Boussy, Tim; Duytschaever, Mattias; Vernemmen, Ingrid; Schauvlieghe, Stijn; Decloedt, Annelies; van Loon, Gunther
Abstract: Background: Atrial tachycardia (AT) can be treated by medical or electrical cardioversion but the recurrence rate is high. Three‐dimensional electro‐anatomical mapping, recently described in horses, might be used to map AT to identify a focal source or reentry mechanism and to guide treatment by radiofrequency ablation. Objectives: To describe the feasibility of 3D electro‐anatomical mapping and radiofrequency catheter ablation to characterize and treat sustained AT in horses. Animals: Nine horses with sustained AT. Methods: Records from horses with sustained AT referred for radiofrequency ablation at Ghent University were reviewed. Results: The AT was drug resistant in 4 out of 9 horses. In 8 out of 9 horses, AT originated from a localized macro‐reentrant circuit (n = 5) or a focal source (n = 3) located at the transition between the right atrium and the caudal vena cava. In these 8 horses, local radiofrequency catheter ablation resulted in the termination of AT. At follow‐up, 6 out of 8 horses remained free of recurrence. Conclusions and Clinical Importance: Differentiation between focal and macro‐reentrant AT in horses is possible using 3D electro‐anatomical mapping. In this study, the source of right atrial AT in horses was safely treated by radiofrequency catheter ablation.